The Effect of Sustainability Committee, Leverage, and Firm Size on Material Disclosure - Bintang Ghani Nugroho; Erna Hernawati (Politeknik Siber Cerdika Internasional, 2026)
Sustainability reporting has become increasingly important for Fast-Moving Consumer Goods (FMCG) companies because their business activities rely heavily on packaging materials that contribute to plastic waste generation and environmental degradation. In ASEAN countries, this issue has become more urgent as several nations face significant challenges related to marine plastic pollution and waste management. This study aims to examine the effects of the Sustainability Committee, leverage, and firm size on material disclosure based on GRI 301 among FMCG companies listed on five Southeast Asian stock exchanges. This research employed a quantitative approach using secondary data obtained from sustainability reports, integrated reports, and annual reports of FMCG companies listed on the Philippine Stock Exchange, Bursa Malaysia, the Indonesia Stock Exchange, the Ho Chi Minh Stock Exchange, and the Stock Exchange of Thailand during the 2014–2023 period. The sample consisted of 231 companies with 1,635 firm-year observations selected through purposive sampling, and the data were analyzed using multiple linear regression analysis. The findings revealed that the Sustainability Committee and firm size had positive and significant effects on material disclosure, indicating that stronger sustainability governance mechanisms and larger organizational scale encourage greater transparency. However, leverage did not have a significant effect on material disclosure. This study concludes that governance structures and firm size are important determinants of material disclosure among ASEAN FMCG companies.